I Viva La Muerte ! : Kunst und Tod in Lateinamerika. - Paz, Octavio; Borges, Jorge Luis, 1899-1986.; Buarque, Chico; Bunuel, Luis; Cortàzar, Julio; Gallindo, Regina José; Garcia Marquez, Gabriel; Matt, Gerald; Miessgang, Thomas; Paz, Octavio; Reyes, Pedro; Schmidt, Bastienne; et al. (Wien : Kunsthalle Wien, 2007)
Allora & Calzadilla ; Alys, Francis ; Amorales, Carlos ; Dr. Lakra ; Echavarria, Juan Manuel ; Edeza, Ivan ; Gallindo, Regina José ; Garcia Rodero, Cristina ; Guzman, Daniel ; Lieberman, Ilán ; Lugbauer, Stephan ; Macchi, Jorge ; Margolles, Teresa ; Meireles, Cildo ; Mendieta, Ana ; Metinides, Enrique ; Muniz, Vik ; Orozco, Gabriel ; Pastorino, Esteban ; Restrepo, José Alejandro ; Reyes, Pedro ; Schmidt, Bastienne ; Sierra, Santiago ; Smith, Melanie
Viva La Muerta ! : Kunst und Tod in Lateinamerika, Las Palmas de Gran Canaria, 2007-10-17 tot 2008-04-18, Kunsthalle Wien, 2008-02-17 tot 2008-06-29
boek
Keywords: Latijns Amerika